Patterns of work - Condon, Judith. 4 0 16; 5 (New York : Franklin Watts, 1992)
Examines new trends in the work force due to unemployment, new technology, changing roles in family life, and increased longevity.
Includes index.
Keywords: 2 -- 0; 6; Labor market;Unemployment;Technological innovations;Families;Longevity;Work.;Labor. -- 20 -- Juvenile literature.;Juvenile literature.;Juvenile literature.;Juvenile literature.;Juvenile literature; 20; 2